2018
DOI: 10.1002/mc.22815
|View full text |Cite
|
Sign up to set email alerts
|

Identification of metabolites in plasma for predicting survival in glioblastoma

Abstract: Circulating metabolomics profiling holds prognostic potential. However, such efforts have not been extensively carried out in glioblastoma. In this study, two-step (training and testing) metabolomics profiling was conducted from the plasma samples of 159 glioblastoma patients. Metabolomics profiling was tested for correlation with 2-year overall and disease-free survivals. Arginine, methionine, and kynurenate levels were significantly associated with 2-year overall survival in both the training and testing set… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 34 publications
0
19
0
Order By: Relevance
“…Circulating-metabolite-based prognostic models have previously been shown to have its promising clinical applications in several cancers, such as glioblastoma (34), non-small cell lung cancer (35), and esophageal adenocarcinoma (24). However, the previous metabolomic studies of ESCC solely focused on the diagnostic value of the metabolites and rarely assessed their prognostic significance.…”
Section: Discussionmentioning
confidence: 99%
“…Circulating-metabolite-based prognostic models have previously been shown to have its promising clinical applications in several cancers, such as glioblastoma (34), non-small cell lung cancer (35), and esophageal adenocarcinoma (24). However, the previous metabolomic studies of ESCC solely focused on the diagnostic value of the metabolites and rarely assessed their prognostic significance.…”
Section: Discussionmentioning
confidence: 99%
“…Presence of the IDH mutation led to higher levels of N -acetylputrescine, trimethylamine- N -oxide, niacin, arginine, glucosamine, and methionine in the plasma [ 210 ]. Plasma metabolomics was also used to predict the GBM patient survival, and higher levels of arginine and methionine are correlated with increased probability of survival, while higher levels of kynurenate with decreased probability [ 211 ]. An exploratory plasma NMR metabolomics study indicated that the levels of creatine, citrate, glucose, pyruvate, and glutamine can be used to discriminate between primary brain tumor patients (among them GBM patients) and healthy controls [ 212 ].…”
Section: The Metabolome—a Way Of Diagnosis and Prognosis Of Gliomamentioning
confidence: 99%
“…Compared with m / z 477.3938 and m / z 441.3727 from RPDQ, the diagnostic ion m / z 493.3866 and m / z 457.3649 was 16 Da higher than them. Therefore, M2 was identified as an oxidrolysis metabolite of RPDQ [ 25 ].…”
Section: Resultsmentioning
confidence: 99%